Translation and psychometric properties of the MISSCARE survey-Persian version - Zeinab Hosseini; Leila Raisi; Amirhossein Maghari; Mansoureh Karimollahi (BMC, 2022)
Abstract Background Providing safe and high-quality nursing care is an essential task of nursing. Nurses may be unable to provide patients with all of the necessary care for numerous reasons, such as an increase in the number of patients and a low number of nursing staff. Moreover, they may have to omit, postpone, or incompletely perform a series of care, referred to as missed nursing care. The purpose of this study was to translate and conduct psychometric testing of the MISSCARE Survey. Method In this study, we accurately translated the MISSCARE Survey. Its acceptability, construct validity, and internal consistency were analyzed. This cross-sectional study was conducted in the summer of 2020 in educational hospitals in Ardabil, Iran. The participants were 300 nurses who worked in educational hospitals and were randomly selected. Results Participants in this study included 300 nurses from five units, including general medicine (13.3%), COVID-19 (45.0%), surgery (18.7%), critical care unit (6.3%), and intensive care unit (16.7%), who worked various shifts, of whom 84.7% were female. The total content validity in Part A was 0.944, and that in Part B was 0.969. Part A was divided into three domains (necessary care, secondary care, and supportive care), and Part B was divided into five domains (communication, labor resources, material resources, responsibility, and unpredictable situations). In both parts, the chi-square index was < 3, and the RMSEA index was < 0.08. The internal consistency measured by Cronbach's alpha was 0.933 for Part A and 0.910 for Part B for the Persian version of the MISSCARE Survey. Conclusion Based on the outcomes of this research, it can be concluded that the Persian version of the MISSCARE Survey is valid for use in Iranian hospitals and can be used to identify missed care and the reasons behind it. Nursing managers can also use it to improve the situation and provide the highest-quality care.